Institutional Ownership, Tax Planning And Tax Avoidance Effect On Firm Value - Angelina Siti Juliani; Endah Finatariani (LPPM ISNJ Bengkalis, 2023)
This research aims to analyze and obtain empirical evidence of the influence of institutional ownership, tax planning, and tax avoidance on firm value. This type of research is associative quantitative, and the data sources used are secondary data in the form of annual financial reports and annual reports. The research population is infrastructure sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period, consisting of 45 companies, while the research sample is 16 companies with five years of observation, and the sample determination method used is purposive sampling. The analytical method used is panel data regression analysis with a fixed effects model using E-views version 12. The results of this study show that institutional ownership positively affects firm value, while tax planning and tax avoidance do not affect on firm value. Then, institutional ownership, tax planning, and tax avoidance variables simultaneously influence firm value. This research can complement existing theories and become a reference in helping companies consider what factors can influence or increase firm value.